Palm Sugar Marketing Strategy in Improving Community Welfare in Kunyi Village, Anreapi Sub-District - Kasmawati; Dambe, Jumriani; Hikmah, Aulia Nurul (Tarjih : Agribusiness Development Journal, 2025)
Palm sugar is one of the commodities that has the potential to be developed in West Sulawesi, especially in Polewali Mandar Regency This study aims to determine and analyze the marketing strategy of palm sugar in Kunyi Village, Anreapi District, Polewali Mandar Regency. This study uses a qualitative method with primary and secondary data collection with the data analysis method used in this study, namely the 7P Marketing Mix analysis. The results of the study indicate that palm sugar farmers in Kunyi Village do not yet have an effective marketing strategy to increase palm sugar sales. They face marketing constraints such as unstable selling prices and want to improve their marketing capabilities. This study recommends the development of effective marketing strategies, mentoring training programs, improving infrastructure, cooperation with stakeholders, and developing more diverse and quality palm sugar products to increase palm sugar sales and improve the welfare of the Kunyi Village community.